Songs as elements in the generic structure of film musicals - Plemenitaš, Katja (ELOPE (Ljubljana), 2016)
The paper focuses on the description of film musicals as a subgenre of the genre family of musicals. Their dramatic structure is examined in terms of the generic elements that constitute the progression of a story expressed through the combination of spoken dialogue, songs and dance. The function of songs in the generic structure of film musicals is examined in the framework of the systemic-functional theory of register and genre. Special attention is given to the role of songs in the unfolding of the narrative. The theoretical observations about the role of songs in the register and genre of film musicals are then illustrated with an analysis of the use of songs in the TV musical High School Musical 2.
Keywords: filmski muzikal; pesmi; sistemsko-funkcijsko jezikoslovje; žanri; žanrska struktura